Exclamatory sentences as the highest manifestation of emotional expression in Ukrainian economic discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article investigates the expressive syntax economic discourse. The characteristic for the different types of scientific speech of exclamatory sentences. Is revealed expressive displayed potential of exclamatory sentences in scientific texts economic discourse on the material of the Ukrainian magazine «The Economist».
Keywords: expressive; syntax; economic discourse; scientific speech; exclamatory sentences